Roland Barthes Semiotics Study in Gojek Indonesia's Ramadan Edition Advertisement and Its Implications for Indonesian Language Learning in High School - Nuraeni, Intan; Munaris, Munaris; Pratama, Aditya; Samhati, Siti (Madiha Press, 2025)
This study focuses on Roland Barthes' semiotic analysis of Gojek Indonesia's Ramadan edition advertisements and their implications for Indonesian language learning in high schools. The purpose of this study is to reveal the denotative, connotative, and mythical meanings in advertisements and their relevance to persuasive text learning. This study uses a descriptive qualitative approach with data in the form of visual and verbal signs from advertisements uploaded through the official YouTube channel. Data collection techniques were carried out through documentation and recording. The results show that the advertisement contains denotative, connotative, and mythical meanings that represent the social and cultural values of Ramadan. These findings are implied as teaching materials for persuasive texts in high school in accordance with the Merdeka Curriculum for Grade XI Phase F. The use of advertisements as a learning medium helps improve students' critical thinking skills regarding persuasive language and encourages the use of polite, rational, and contextual language.